The patent services of the institutions of higher education — one of the key elements in formation and realization of the government politics of Russian economical rise - N. G. Zubareva (Бюллетень сибирской медицины, 2002)
The process of formation of a single government politics in the sphere of industrial property is discussed. It is pointed out that economical significance of the objects of IP is rising because of priority orientation of the Russian science and industry on making scientific, good production. The questions of effective legal protection and commerce realization of the IP objects are also touched. It is settled that support and development of the patent service in the institutions of higher education are necessary.